2003
DOI: 10.1046/j.1538-7836.2003.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of von Willebrand factor activity: relative effects of ABO blood type and race

Abstract: Summary. Tests based on three different principles are reported to measure the activity of von Willebrand factor (VWF): ristocetin cofactor (VWF:RCo), collagen binding (VWF:CB), and the so-called`activity ELISA' (VWF:MoAb). We measured these and other diagnostic parameters in a population of 123 randomly selected female study controls, age 18±45 years. Type O subjects had signi®cantly lower levels than non-O subjects in each test. Race differences were seen in all tests except VWF:RCo, with Caucasians having s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
111
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 38 publications
8
111
1
2
Order By: Relevance
“…VWF: CB was significantly lower in blood group O when compared with non-O blood. This is consistent with the observation in the Chinese population (Chng et al, 2005), Australia (Favaloro et al, 2005) and Atlanta (Miller et al, 2003). In this study, we also demonstrated a significant correlation between VWF: Ag and VWF: CB in blood group O subjects.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…VWF: CB was significantly lower in blood group O when compared with non-O blood. This is consistent with the observation in the Chinese population (Chng et al, 2005), Australia (Favaloro et al, 2005) and Atlanta (Miller et al, 2003). In this study, we also demonstrated a significant correlation between VWF: Ag and VWF: CB in blood group O subjects.…”
Section: Discussionsupporting
confidence: 93%
“…The actual ranges quoted by earlier reports varied greatly, this may be attributed to the genotype of the ABO blood group and other factors outside the VWF gene. The ranges determined in this study were higher when compared with Caucasian values determined by Miller et al (2003). This may be explained because VWF is an acute phase reactant in man and our population is exposed to many conditions including malaria infestation that can predispose to an inflammatory response.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Alternatively, an unidentified genetic or environmental factor, with distinct frequencies between individuals of European and African descent, may modify the ABO-AKI association depending on race. For example, polymorphisms in the vWF gene are associated with expression of vWF in healthy Americans of European but not African descent, suggesting racial divergence in the genetic regulation of vWF expression (46,47) and possibly, contributing to the racial difference in ABO-AKI associations. The baseline characteristics of our cohorts also exhibit racial differences.…”
Section: Discussionmentioning
confidence: 99%